PRODUCTION AND QUALITY OF EGGS QUAILS GIVEN STAR FRUIT LEAVES EXTRACT THROUGH DRINKING WATER - R. Y., Rumngevur; Wirapartha, M.; Umiarti, A. T. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
The study was conducted to determine the quality of quails eggs ( Coturnix coturnix japonica ) given the extract of star fruit leaves ( Averrhoa bilimbi L. ) through drinking water.  The research was carried out at Sesetan Teaching Farm and Poultry Livestock Laboratory, Animal Husbandry, Faculty of Udayana University, and was carried out for four weeks.  The research design used was a complete randomized design (RAL) with four treatments and four replications. Each replications uses four Japanese quails, bringing the total number of quails used to 64.   The treatments are quails which given drinking water without star fruit leaf extract (R0) as a control, given drinking water with 2%, 4%, and 6% star fruit leaf extract as treatment R1, R2 and R3.  The variables observed are: egg weight, egg pH, HU ( Haugh Unit ), yolk colour, and egg index.  The results showed that the eggs weight, egg pH, yolk colour, and egg index in the four treatments were statistically not significantly different (P>0.05).  In the egg production variables in the R1, R2, R3 treatment, it was significantly higher (P<0.05) than the R0 treatment.  In the HU ( Haugh Unit ) and colour of egg yolk variable in the R2 treatment, it was significantly higher (P<0.05) than the R3 treatment.  Based on the results of the study, it can be concluded that giving star fruit leaf extract at the level of 2%, 4%, and 6% through drinking water in quails ( Coturnix coturnix japonica ) aged 7-11 weeks can increase egg production, maintaining good egg quality in haugh units with grade AA.   In the quality of the yolk colour at the control, level 2%, and 4% get the same good yolk colour. Keywords: Japanese quail, star fruit leaf, egg quality, drinking water